Unequal contribution of two paralogous CENH3 variants in cowpea centromere function - Ishii, Takayoshi (Commun Biol, 2020)
In most diploids the centromere-specific histone H3 (CENH3), the assembly site of active centromeres, is encoded by a single copy gene. Persistance of two CENH3 paralogs in diploids species raises the possibility of subfunctionalization. Here we analysed both CENH3 genes of the  diploid dryland crop cowpea. Phylogenetic analysis suggests that gene duplication of CENH3 occurred independently during the speciation of Vigna unguiculata. Both functional CENH3 variants are transcribed, and the corresponding proteins are intermingled in subdomains of different types of centromere sequences in a tissue-specific manner together with the kinetochore protein CENPC. CENH3.2 is removed from the generative cell of mature pollen, while CENH3.1 persists. CRISPR/Cas9-based inactivation of CENH3.1 resulted in delayed vegetative growth and sterility, indicating that this variant is needed for plant development and reproduction. By contrast, CENH3.2 knockout individuals did not show obvious defects during vegetative and reproductive development. Hence, CENH3.2 of cowpea is likely at an early stage of pseudogenization and less likely undergoing subfunctionalization.